2015
DOI: 10.1158/0008-5472.can-15-0708
|View full text |Cite
|
Sign up to set email alerts
|

PI3K–mTORC2 but not PI3K–mTORC1 Regulates Transcription of HIF2A/EPAS1 and Vascularization in Neuroblastoma

Abstract: Hypoxia-inducible factor (HIF) is a master regulator of cellular responses to oxygen deprival with a critical role in mediating the angiogenic switch in solid tumors. Differential expression of the HIF subunits HIF1a and HIF2a occurs in many human tumor types, suggesting selective implications to biologic context. For example, high expression of HIF2a that occurs in neuroblastoma is associated with stem cell-like features, disseminated disease, and poor clinical outcomes, suggesting pivotal significance for HI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
4
75
0
Order By: Relevance
“…Cells were lysed in RIPA buffer supplemented with Complete Protease Inhibitor (Roche, Basel, Switzerland) and phosSTOP (Roche) as previously described (Mohlin et al , ). Proteins were separated on SDS–PAGE gels and transferred to PVDF‐ or Hybond‐C extra nitrocellulose membranes (Bio‐Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were lysed in RIPA buffer supplemented with Complete Protease Inhibitor (Roche, Basel, Switzerland) and phosSTOP (Roche) as previously described (Mohlin et al , ). Proteins were separated on SDS–PAGE gels and transferred to PVDF‐ or Hybond‐C extra nitrocellulose membranes (Bio‐Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Current treatment strategies include high-dose chemotherapy, surgery, radiotherapy, and anti-GD2 therapy. We and others have shown that targeting the PI3K/mTOR pathway could be a viable treatment for aggressive neuroblastoma (Chesler et al, 2006;Johnsen et al, 2008;Segerström et al, 2011;Chanthery et al, 2012;Mohlin et al, 2013Mohlin et al, , 2015Cage et al, 2015;Stewart et al, 2015;Vaughan et al, 2016). Several studies reported anti-tumor effects and improved survival rates in preclinical neuroblastoma models using PI3K inhibitors LY294002 (Chesler et al, 2006), PI-103 (Segerström et al, 2011), dactolisib/NVP-BEZ235 (Chanthery et al, 2012;Stewart et al, 2015;Vaughan et al, 2016), ZSTK474 (Vaughan et al, 2016), PIK-75 (Cage et al, 2015), PW-12 (Cage et al, 2015), BKM120 (Stewart et al, 2015), and/or SF1126 (Erdreich-Epstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that inhibition of hypoxia-driven LIMD1 expression, resulting in enhanced HIF-a protein stability, drives HIF2A mRNA expression. Stabilisation of HIF-a protein and hypoxia has previously been described as inducers of HIF2A mRNA expression Mohlin et al, 2015). Many HIF-activated genes have been identified as prognostic and diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, methylated CpG binding protein 3 binds to the EPAS1 promoter and enhances its transcription by demethylating CpG located around transcriptional start site, causing the activation of HIF‐2α‐mediated angiogenesis (Cui et al, ). In addition, it has been reported that EPAS1 transcription is regulated by the IGF‐induced PI3K‐mTORC2 system promoting vascularization in neuroblastoma (Mohlin et al, ). The deubiquitylase Cezanne (also known as OTUD7B) is also involved in the regulation of HIF‐2α mRNA synthesis via E2F1, which directly binds to the EPAS1 promoter (Moniz et al, ).…”
Section: Hypoxia‐inducible Factor‐2mentioning
confidence: 99%